Islam, peace and social justice : a Christian perspective - Van Gorder, A. Christian (James Clarke, 2014)
Our world is fraught with horrific expressions of violence and injustice, which are often justified by religious rhetoric. 'Islam, Peace, and Social Justice: A Christian Perspective' is a relevant, comprehensive, and empathetic examination of some of these social-justice challenges within the Muslim world. Sadly, many non-Muslims only learn about Muslim views on social-justice issues from biased and inaccurate media portrayals. This book, written by a non-Muslim friend of Muslims, offers a more sympathetic and nuanced treatment, focusing especially on points of convergence and divergence betwe.